Analisis Variasi Panjang Kabel Busi Terhadap Motor Bensin 4 Langkah - Idrys, Da'im; , Ir. Sartono Putro, MT; , Ir. Sunardi Wiyono, MT (2016)
Besides the octane number and the mixture of air and fuel which enter the combustion chamber, the ignition system also has an influence on the performance of 4 stroke SI engine. One of components in the ignition system is a coil which functions as increasing the voltage received from the battery into a higher voltage. The higher voltage is then connected to the spark-plug with a wire commonly known as the spark-plug wire. In the spark-plug wire, the amount of resistance is directly proportional to the wire length. The longer the spark-plug wire, the more the resistance will be. To deal with this matter, the wire of the spark-plug which is used is made shorter in order to reduce the resistance. In this research, the coil which was used was the standard coil of Yamaha Jupiter Z Motorcycle, Moric-brand with a code of 4 ST which used a spark-plug wire length of 18 cm. In the testing, a variation of spark-plug wire length was conducted into 3, that was from the previous length of 18 cm shortened into 9 cm (50%) and 4.5 cm (25%). The result of the testing revealed that the best performance of 4 stroke SI engine was obtained from the use of coil with a spark-plug wire length of 25%. From the testing, it was found the result of torque as much as 8.68 Nm on 5000 rpm and power as much as 8.0 Hp on 7750 rpm and the result of the testing of SFC as much as 0.078 Kg/h.Hp.